Her place at the table : a woman's guide to negotiating five key challenges to leadership success - 297033 Kolb, Deborah M.; Williams, Judith, 1942-; Frohlinger, Carol, 1953- (San Francisco, Calif. : Jossey-Bass, 2004)
PSZJBL